Disguise and Role-playing in Ben Jonson's Drama - Hyland, Peter (My University, 1973)
Because of their obvious value in plot-complication, disguise-devices were very popular amongst Renaissance play-wrights; occasionally they were used with freshness and originality, but more often did not escape the dullness of convention. Disguise figures prominently in Jonson's comedy, and a close examination of the way in which the dramatist employs disguise demonstrates that he endows it with a particular significance that is consistent throughout his dramatic career. Jonson's affection for Stoic doctrine is well known, and he is especially concerned with that part of the doctrine that sees it as a man's moral duty to create an identity for himself and to remain constant to it. The foolish or vicious man is characterized by his unwillingness to accept such identity, or his inability to create it, by his preference for the mask. Putting this metaphor into action, Jonson creates a satiric world of disguisers and role-players, of men who create an illusion of themselves by a change in appearance, or by verbal disguise. But there is always a moral weight attached to the use of disguise: a disguise is criticized for that very activity. A chronological examination of the plays demonstrates how critical the disguiser, looking real identity, is to Jonson's moral vision, and further demonstrates how little this vision changed throughout his career. More important, an understanding of the function of the disguiser is helpful, and often crucial, for an understanding of the ethical direction of the plays. For Jonson's world is generally a world without norms, a world entirely made up of villains, where wit rather than morality seems to be triumphant. But the disguiser himself implies a norm, insofar as he implies the alternative possibility of Stoic integrity and authenticity. And although this Stoic figure rarely appears in the plays, he is prominent in Jonson's poetry. An understanding of Jonson's attitude toward the play-actor also helps explain our uneasiness in accepting apparent norms like Truewit and Quarlos, whose triumph is one of wit rather than superior morality; for by their implication in the general role-playing they prove themselves to be, finally, as empty as those they mock. This study substantiates the view that Jonson is always moralist, even when there are no moral spokesman in his plays, and that a clear understanding of his plays requires an understanding of his subtly ironic viewpoint. Indeed, it is those plays which have a moral spokesman that are his least successful. Further, it underlines the unity of his vision, not simply in individual plays, but throughout the body of his work. Finally, it helps explain the disturbing ambiguity which Jonson shows toward his chosen medium, the stage.
Keywords: role-playing; Ben Jonson